Stakeholder Collaboration in Marriage Registration in Bogor Regency, West Java Province: A Study on the Integration of Population Data at the Population and Civil Registration Office (Disdukcapil), the Office of Religious Affairs (KUA), and the Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3AP2KB) of Bogor Regency (International Forum of Researchers and Lecturers, 2025)
Bogor Regency faces a high prevalence of unregistered marriages, influenced by social, economic, and cultural factors, including the presence of foreign nationals in the Puncak area. Around 45.21% of married couples are not legally registered, causing significant issues for children in obtaining birth certificates, inheritance rights, and access to public services. This study aims to identify the factors contributing to the high rate of unregistered marriages, explore the integration of population data through stakeholder collaboration to increase marriage certificate ownership, and assess collaborative efforts to raise awareness about the importance of marriage registration. The study uses stakeholder collaboration theory, which includes goal clarification, tool selection, cost-benefit analysis, and adaptive process management. A descriptive qualitative approach is employed, with data collected through observation, interviews, documentation, and audio-visual materials. The findings indicate that unregistered marriages are mainly due to economic limitations, administrative barriers, a lack of public understanding about the importance of marriage certificates, and inadequate socialization. Population data integration through stakeholder collaboration has led to positive outcomes, especially in tool selection, with shared goals formalized through Cooperation Agreements (PKS) and MoUs, and an effective marriage confirmation process. However, the cost-benefit analysis dimension has not been fully optimized due to the lack of budget allocations in 2024, requiring integration with P2KWSS activities. Additionally, adaptive process management remains challenging due to migration and contract marriages in Cisarua Sub-district. Stakeholder efforts include Integrated Marriage Confirmation, one-day services, inter-agency cooperation, and premarital education and counseling programs.